SOLVING PROBLEMS OF MATHEMATICS LEARNING ON PERCENTAGES AND RATIOS BY USING SKILL - BUILDING EXERCISES FOR PRATHOM 6 STUDENTS AT THANASITANUSORN SCHOOL - Rueangphankun, Thanat (Journal of MCU Nakhondhat, 2023)
The purposes of this study were: 1) to study the efficiency of the skill - building exercises on percentages and ratios; 2) to compare students’ learning achievements between before and after the use of the skill - building exercises on percentages and ratios; and 3) to develop the skill - building exercises on percentages and ratios with an efficiency of (E1/E2) = 70/70. This research was done using a one - group pretest - posttest design. The sample group of this study, selected using purposive sampling, was 28 Prathom 6 students at Thanasitanusorn School, Bang Phli, Samut Prakan. The research instrument included six sets of the skill - building exercises on percentages and ratios, as well as the pre - test and post - test on ratios and percentages. The statistics used to analyze the collected data were ratios and means. It was found that 1) The mean score of the students after learning using the skill - building exercises on percentages and ratios went up, which demonstrated that such exercises had efficiency according to the criteria set. 2) As for the learning achievement tests, students scored better after the use of the skill - building exercises on percentages and ratios in their learning, meaning the skill - building exercises resulted in the expected results. 3) The skill - building exercises on percentages and ratios had an efficiency of (E1/E2) = 70/70, which meant they were created and developed using appropriate methods and a systematic process. They were also proven and revised before implementation, which led to an efficiency in the determined range of 70/70.